Avaliação de ciclo de vida de embalagens plásticas de óleo lubrificante: um estudo de caso - Oliveira, Maria Clara Brandt Ribeiro de (2017)
This thesis uses life cycle assessment methodology to evaluate the environmental impacts of lubricant oil plastic containers (LOPCs), from production to final disposal. Various scenarios are compared which use different combinations of quantities of LOPCs destined to recycling, to incineration with energy production (waste-to-energy) and to disposal in industrial landfills. The phases of the reverse logistic implemented by the Instituto Jogue Limpo were also analyzed in order to find bottlenecks and identify possible improvements. Results show that the decrease in the amount of LOPCs being sent to industrial landfills can lead to important reductions in environmental damages produced during their life cycle. Although the waste-to-energy option is not currently adopted in Brazil for the disposal of this kind of waste, the analysis indicates that it is a promising technology when combined with recycling as a treatment option for LOPCs. The combination of different destinations may produce good options, but the final choice depends on economic, logistic e environmental considerations. This study can help defining alternative choices related to waste management of LOPCs, especially in the development of industrial strategies and in the decision-making process related to environmental questions. This thesis concludes that developing countries can manage hazardous waste effectively. However, it takes time, political determination and adequate legislation, together with a cooperative posture of the private sector to accomplish desired results.